National Seminar on the New International Economic Order and UNCTAD-IV, November 17-20, 1975 : implications for India - Babu, V. Vittal (Indian Institute of Foreign Trade, 1975)
Comprises papers and proceedings of a seminar organized by the Indian Institute of Foreign Trade, New Delhi.